Pengaruh Return On Assets(ROA),Return On Equity(ROE) Dan Net Interest Margin(NIM) Terhadap Harga Saham Pada Bank BCA Tbk - Agus Tri Indah K; harun Al Rasyid (Politeknik Ganesha Medan, 2022)
This study was conducted to analyze the effect of Return On Assets (ROA), Return On Equity (ROE) and Net Interest Margin (NIM)) on Stock Prices with the object of PT Bank Central Asia, Tbk for the period 2015 to 2021 quarterly. The independent variables in this study are represented by Return On Assets (ROA), Return On Equity (ROE), Net Interest Margin (NIM)). The data collection method used is the library research method. The data analysis technique used is multiple linear regression and hypothesis testing using t-statistics to partially test each variable. The results of the t-test can be seen in the coefficients table in the sig column (significance), as well as F-statistics to test the effect of the independent variables simultaneously (simultaneously) on the dependent variable with a significance level of 5 percent. The data is processed using the SPSS program. The results show that partially ROA(X1) is Tcount(3.129) > Ttable(2.064), then it has a positive effect on Stock Price(Y), For ROE(X2) is Tcount(-2.677) < Ttable(2.064), then it has no effect negative to the Stock Price (Y). and for NIM(X3) is Tcount(0.708) < Ttable(2.064), then it has no positive effect on Stock Price(Y). For Simultaneous calculation (Test Statistics F), then t table of simultaneous test results Fcount(4.418) > Ttable(2.99) , then the conclusion ROA(X1), ROE(X2)d and NIM(X3) simultaneously affect stock prices (Y). For the Coefficient of Determination (R²), the independent variable affects the health level of BCA Bank as much as 35.6%, and the remaining 64.4% is affected by other variables. And it can be seen that the adjusted R square is 0.275, which means that 27.5% has an effect on stock prices while 72.5%% is determined by other variables that are not explained by this research model, which is summarized in the error.